MicroRNA-221 restricts human cytomegalovirus replication via promoting type I IFN production by targeting SOCS1/NF-κB pathway. Issue 22 (17th November 2019) - Yan, Beizhan; Ma, Huimin; Jiang, Shuting; Shi, Jingli; Yang, Ziyi; Zhu, Weiyan; Kong, Cunquan; Chen, Lin; Yan, Hui; Ma, Cuixia
ABSTRACT: HCMV is a common pathogen for human with relatively high prevalence, which could be life-threatened in immunodeficient patients and lead to significant birth defects in newborns. In this study, we firstly report that HCMV infection significantly enhances the expression of microRNA-221 (miR-221) in Neural Precursor Cells (NPCs). We found that miR-221 directly targets at the 3ʹ-UTR of suppressor of cytokine signaling 1 (SOCS1) and suppresses SOCS1 expression at the both mRNA and protein levels. MiR-221 overexpression restrained HCMV replication by promoting type I interferon (IFN) and interferon stimulating genes (ISGs) production, whereas reintroduction of SOCS1 abrogated the miR-221-induced effects on HCMV replication. Importantly, miR-221 positively regulated the phosphorylation and activation of NF-κB by suppressing SOCS1. What's more, miR-221 agomir alleviated MCMV-induced tissue injury by promoting type I IFN antiviral activities in vivo. Thus, miR-221 modulates the infection and replication of HCMV as an intrinsic antiviral factor, and could be developed as a treatment target for anti-HCMV treatment.